Teaching Speaking by Using Student Facilitator and Explaining Strategy - Nelly Mursyidah; Asnawi Muslem; Siti Sarah Fitriani (English Education Journal, 2018)
This study was aimed to investigate the effect of Student Facilitator and Explaining Strategy in teaching speaking in terms of fluency and grammar at the second grade students of MAS Al Zahrah Bireuen in academic year 2017/2018. The research is an experimental research. The sample of the research was two classes; experimental (xib) and control classes (xic). Both classes consisted 25 students. The technique of choosing the samples was random sampling. The data were collected through tests and questionnaire. The data were analyzed by using SPSS 23 to find t-test score between two classes and the data from questionnaire to find the students’ responses toward the use Student Facilitator and Explaining Strategy of experimental class. Based on data analysis, the result of t-test of fluency is 2.48 and grammar is 3.84 are higher than t-table (2.01). Than, students had a quite positive responses (80%) toward the use of Student Facilitator and Explaining Strategy in terms of fluency and grammar. Therefore, it could be concluded that Student Facilitator and Explaining Strategy effectively improved students’ achievement in speaking skill in terms of fluency and grammar.